Skeletal dysmorphology and mineralization defects in Fgf20 KO mice - Dlugosova, Sylvie; Spoutil, Frantisek; Madureira Trufen, Carlos Eduardo; Melike Ogan, Betul; Prochazkova, Michaela; Fedosieieva, Olha; Nickl, Petr; Aranaz Novaliches, Goretti; Sedlacek, Radislav; Prochazka, Jan (Frontiers in Endocrinology, 2024)
Fibroblast growth factor 20 (Fgf20), a member of the Fgf9 subfamily, was identified as an important regulator of bone differentiation and homeostasis processes. However, the role of Fgf20 in bone physiology has not been approached yet. Here we present a comprehensive bone phenotype analysis of mice with functional ablation of Fgf20. The bone phenotype could be detected especially in the area of the lumbar and caudal part of the spine and in fingers. Regarding the spine, Fgf20 -/-mice exhibited adhesions of the transverse process of the sixth lumbar vertebra to the pelvis as well as malformations in the distal part of their tails. Preaxial polydactyly and polysyndactyly in varying degrees of severity were also detected. High resolution microCT analysis of distal femurs and the fourth lumbar vertebra showed significant differences in structure and mineralization in both cortical and trabecular bone. These findings were histologically validated and may be associated with the expression of Fgf20 in chondrocytes and their progenitors. Moreover, histological sections demonstrated increased bone tissue formation, disruption of Fgf20-/-femur cartilage, and cellular-level alterations, particularly in osteoclasts. We also observed molar dysmorphology, including root taurodontism, and described variations in mineralization and dentin thickness. Our analysis provides evidence that Fgf20, together with other members of the Fgf9 subfamily, plays a crucial regulatory role in skeletal development and bone homeostasis.